Concepts and conjectures concerning predatory performance of myxobacteria - Phillips, Kayleigh E.; Akbar, Shukria; Stevens, D. Cole (Frontiers in Microbiology, 2022)
Myxobacteria are excellent model organisms for investigation of predator–prey interactions and predatory shaping of microbial communities. This review covers interdisciplinary topics related to myxobacterial predation and provides current concepts and challenges for determining predatory performance. Discussed topics include the role of specialized metabolites during predation, genetic determinants for predatory performance, challenges associated with methodological differences, discrepancies between sequenced and environmental myxobacteria, and factors that influence predation.